Guerra e identidade: um estudo da marcialidade no Heimskringla - Miranda, Pablo Gomes de (2013)
The goal of our dissertation is to study how the Scandinavian writings produced a Norwegian identity of warlike ideals in a compilation of Icelandic sagas known as Heimskringla and has parts of its content focused on storytelling about a troubled time of Scandinavian monarchies rising between the 8th and 11th centuries, which is called the Viking Age. The Heimskringla, also known as The Circle of the World is a set of writings based on Icelandic oral memory about the Norwegian kings and the conception of a Norwegian territory. While we investigated the relationship between the members of royalty, their companions and the Scandinavian people, we delineate the relationship between memory, identity and war. Our study points out how the Scandinavian war produces, in its storytelling, proper spaces, in socio-political relations among the participants, in the organization of its conflicts or the location of war activities, where places are transformed into essential points in these narratives. The war is both a place of identity statements and a space of practices, necessary for the strengthening of royal power